Readiness to Change in Higher Education: Do Demographic Differences in Psychosocial Predictors Matter? - Amy Mardhatillah; Shukran Abdul Rahman (Jurnal Psikologi Sosial, 2020)
The study aims to (1) examine demographic differences in higher education employee’s readiness to change, and (2) Identify whether several psychosocial predictors affect higher education employee’s readiness to change across different demographic backgrounds. A total of 214 academics and 214 non-academic staff participated in this study. 34.84% of the respondents were in the age range of 31-40 years old, 30.31% in the age range of 41-50 years old. 20.76% were between 21-30 years old, and 14.08% were 51 years and above. 64.44% consists of female respondents, while 35.56% are male respondents. We found that there was a statistically significant difference in the scores of employees’ readiness to change based on gender and age. Openness to experience, management support, and perceived appropriateness of change also significantly predicted employees’ readiness for change, particularly among non-academic staff. Meanwhile, change efficacy significantly predicted readiness for change among academics. Individual spirituality significantly predicted readiness to change for older employees than younger employees. The study shed light on the possible design for an intervention program in order to enhance employees’ readiness to change in the context of the higher learning institution. Organizational change initiatives may show the potential to be implemented in a higher learning institution.